A Citizen Science Trial to Assess Perception of Wild Penguin Welfare - Freire, Rafael; Massaro, Melanie; McDonald, Simon; Trathan, Philip; Nicol, Christine J. (Frontiers in Veterinary Science, 2021)
Wild penguins are facing increased threats to their populations and their welfare as a consequence of human activities. Understanding the perception of animal welfare is essential to identify ethical concerns related to the negative impact of anthropogenic factors on wild species and to guide conservation efforts that reflect societal values. Since penguin conservation is of general interest, we examined the human dimension of welfare assessment across a range of interest groups concerned with penguins, seabird biology and wildlife conservation. We provided participants with a Penguin Welfare Assessment Tool (PWAT) based on the five domains model. The PWAT supports consideration of the impact of four physical aspects on welfare-relevant mental states. Bibliometric analysis of keywords from 347 scientific articles indicated that penguins around the world face five main types (themes) of anthropogenic factors and we then developed five hypothetical scenarios, each related to one theme. Seventy-five participants scored the overall impact of the events described in the scenarios on penguin welfare as negative using the PWAT. Participants rated short-duration, high-intensity events (i.e. being trapped in a ghost fishing net) as having a significantly more severe impact on penguin welfare than low-intensity, long-duration events (P<0.0001). Scores provided by participants for each domain for each scenario were largely as expected and we found good correlation (all P<0.0001) between the physical domains and “mental state” for all scenarios, indicating that the tool was facilitating the participants’ assessment of welfare. No evidence was found that experience of working or studying penguins, or indeed any other demographic factor investigated, influenced the assessments of welfare. We found little agreement between participants in the scores provided (unalike scores mostly between 0.7 and 0.8), and agreement between participants with experience of working with penguins was no better than between participants without such experience. We discuss the possibility that low agreement within different interest groups may be improved by providing more scientific information to support the evaluation of penguin welfare. We conclude that scientific knowledge of penguin biological responses to anthropogenic factors is vital to support the evaluation of wild penguin welfare by the public and other stakeholders.